Poor Glycemic Control in Carbapenem-Resistant Klebsiella pneumoniae Infections: Impact on Epidemiological Features, Mortality Risks, and Polymyxin Resistance - Wang Q; Yan T; Ma C; Teng X; Shen C; Wang N; Yu K; Chu W; Zhou Q; Liu Z (Infection and Drug Resistance)
Qiuyan Wang,1 Tao Yan,1 Chengcheng Ma,1 Xuan Teng,1 Chengyin Shen,2 Na Wang,3 Kexue Yu,1 Wenwen Chu,1 Qiang Zhou,1 Zhou Liu1,4 1Department of Clinical Laboratory, The Second Affiliated Hospital of Anhui Medical University, Hefei, Anhui, People’s Republic of China; 2Anhui Province Key Laboratory of Medical Physics and Technology, Institute of Health and Medical Technology, Hefei Institutes of Physical Science, Chinese Academy of Sciences, Hefei, Anhui, People’s Republic of China; 3Institute of Health Sciences and Technology, Institutes of Physical and Information Technology, Anhui University, Hefei, Anhui, People’s Republic of China; 4Department of Clinical Laboratory Center, Anhui Chest Hospital, Hefei, Anhui, People’s Republic of ChinaCorrespondence: Zhou Liu, Email liuzhou0112@ahmu.edu.cnPurpose: This study aims to investigate the relationship between glycemic control and epidemiological characteristics of patients infected with carbapenem-resistant Klebsiella pneumoniae (CRKP), to identify mortality risk factors associated with CRKP infection, and to evaluate the impact of glucose on the resistance of CRKP to polymyxin and serum killing.Patients and Methods: Clinical cases of 218 patients infected with CRKP were collected from a large tertiary public hospital in Anhui Province. We analyzed whether the glycemic control impacts the clinical and laboratory manifestations of infected patients. Logistic regression identified mortality risk factors. Antibiotic sensitivity, capsular serotypes, and virulence genes were tested of the strains. Three clinically isolated CRKP strains were used to investigate the effect of glucose on bacterial capsule synthesis and the impact on bacterial resistance to polymyxin and serum killing.Results: Patients with poor glycemic control experienced more severe infections and had a higher likelihood of chronic kidney disease (CKD) and acute renal insufficiency compared to those with good glycemic control. They also exhibited an increased mortality rate. Logistic regression analysis identified age, glycosylated hemoglobin (HbA1c) ≥ 7%, CKD, tumor, mechanical ventilation, and sepsis as independent risk factors for death associated with CRKP infection. A 0.5% (0.5 g/100mL) glucose environment can stimulate CRKP capsule synthesis, which is inhibitable by cyclic adenosine monophosphate (cAMP). Moreover, a high-glucose environment can enhance CRKP’s resistance to polymyxin and serum killing.Conclusion: A persistent hyperglycemic environment resulting from poor glycemic control may stimulate the synthesis of CRKP capsules, which could enhance the resistance of CRKP to polymyxin and serum killing, thereby further increasing the risk of patient mortality.Keywords: carbapenem-resistant Klebsiella pneumoniae, poor glycemic control, polymyxin, serum resistance, capsule, diabetes